The Effectiveness of Logistic Capability Maintenance Through the Integration of Supply Chain in MK PMBTD - Nurhana Mohamad Rafiuddin, NorashikinSahol Hamid, Nur SurayyaMohdSaudi, Aida Nasirah Abdullah, AmnahSaayah Ismail, Rabi’atul ‘Adawiyah Md Zain, Nora Ibrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
MK PMBTD is responsible for implementing the repair and maintenance of Malaysian Army vehicles. Repair and maintenance of vehicle is carried out in several Repair. These duties and responsibilities are taken up by all MK PMBTD who are stationed in various formations and units. Vehicle repair and maintenance and servicing is the responsibility of the User from their respecting units. So, the maintenance responsibility in the unit is a very important because this is where maintenance or servicing at the level being carried out by the user. Hence, failure to carry out the maintenance and servicing by the respective units should be resolved promptly as failure in the implementation will result in more serious damage for the Army’s vehicle. The objective to determine the level of working culture, attitude, leadership, customer relationship and effectiveness of logistic capability maintenance, to examine the relationship between working culture, attitude, leadership, customer relationship with the effectiveness logistic capability maintenance and to examine the most significance of working culture, attitude, leadership, customer relationship and effectiveness logistic capability maintenance. The scope of this research study is performed on a total of 140 personnel in MK PMBTD and focus on Effectiveness Logistic Capability Maintenance at workplace among personnel of MK PMBTD. Quantitative research methods of the correlational research design were conducted using questionnaires distributed to the 140 respondents from the Malaysian Army in MK PMBTD and analysing using the Statistical Packages for the Social Sciences 26.0. The results for this study of the working culture and effectiveness logistic capability maintenance (r=0.819), attitude and effectiveness logistic capability maintenance (r=0.823), leadership and effectiveness logistic capability maintenance (r=0.882), customer relationship and effectiveness logistic capability maintenance (r=0.819). Then, Leadership standard coefficient Beta demonstrates the highest value 0.291 and the lowest level is customer relationship which is 0.035. However, the influence of these factors is found to be different from one another. Leadership shows the highest impact on effectiveness logistic capability maintenance while customer relationship shows the least impact on effectiveness logistic capability maintenance.